Supply Chain Integration and Quality-Based Management in Dairy Processing Enterprises: Evidence from Uzbekistan - Mukhayyo Tillaeva (International Journal on Economics, Finance and Sustainable Development, 2026)
Dairy processing enterprises play a strategic role in food security, rural income generation and value-added development in agri-food systems. However, their efficiency depends not only on production capacity, but also on the stability of raw milk supply, hygienic control, cold-chain logistics, traceability and market-oriented management decisions. The purpose of this study is to develop an integrated management mechanism for dairy processing enterprises by combining supply chain coordination, quality and safety control, digital monitoring and performance-based decision-making. The study uses systematic literature analysis, comparative analysis, indicator-based assessment and management modelling. The empirical context is Uzbekistan, where the dairy sector has a considerable raw milk base: in January-December 2024, all categories of farms produced 12,443.8 thousand tons of milk, equal to 104.0% compared with the same period of 2023. The proposed model consists of five interrelated blocks: raw milk supply coordination, quality and safety control, cold-chain and logistics management, digital monitoring and market-oriented performance evaluation. The scientific contribution of the article is that it shifts the focus from fragmented production management to an integrated management mechanism suitable for dairy processing enterprises in emerging agri-food markets.